The effect of horizontal gradients and spatial measurement resolution on the retrieval of global vertical NO2 distributions from SCIAMACHY measurements in limb only mode - Puķīte, Jānis; Kühl, S.; Deutschmann, Tim; Dörner, S.; Jöckel, P.; Platt, Ulrich; Wagner, T. (Atmospheric measurement techniques, 2010)
Limb measurements provided by the Scanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) on the ENVISAT satellite allow retrieving stratospheric profiles of various trace gases on a global scale. Combining measurements of the same air volume from different viewing positions along the orbit, a tomographic approach can be applied and 2-D distribution fields of stratospheric trace gases can be acquired in one inversion. With this approach, it is possible to improve the accounting for the effect of horizontal gradients in the trace gas distribution on the profile retrieval. This was shown in a previous study for the retrieval of NO2 and OClO profiles in the Arctic region near the polar vortex boundary. - In this study, the tomographic retrieval is applied on measurements during special limb-only orbits performed on 14 December 2008. For these orbits the distance between consecutive limb scanning sequences was reduced to ~3.3° of the orbital circle (i.e. more than two times with respect to the nominal operational mode). Thus, the same air volumes are scanned successively by more than one scanning sequence also for midlatitudes and the tropics. It is found that the profiles obtained by the tomographic 2-D approach show significant differences to those obtained by the 1-D approach. In particular, for regions close to stratospheric transport barriers (i.e. near to the edge of the polar vortex and subtropical transport barrier) up to 50% larger or smaller NO2 number densities (depending on the sign of the gradient along the line of sight) for altitudes below the peak of the profile (around 20 km) are obtained. - The limb-only measurements allow examining the systematic error if the horizontal gradient is not accounted for, and studying the impact of the gradient strength on the profile retrieval on a global scale. The findings for the actual SCIAMACHY observations are verified by sensitivity studies for simulated data for which the NO2 distributions to be retrieved are known in advance. In addition, the impact of the horizontal distance between consecutive limb scanning sequences on the quality of the tomographic 2-D retrieval is investigated and a possibility to take into account the horizontal gradients by an interpolation approach is studied.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 08.05.2023